Critical moments in freestyle BMX/MTB and their impact on prestart conditions - Siriški, D.; Pacholik, V.; Hrebicková, S.; Mach, J. (Journal of Human Sport & Exercise, 2015)
The purpose of this study was to describe critical moments in freestyle competition, analyse mental state of elite freestyle cycling athletes before competition and to evaluate changes of their subjective psychological experiences. In our research we compared results of freestyle cyclists with results of reference group of elite track cyclists. We used semi-structured interviews and two standardized questionnares: SUPSO test and SPARO test. Statistically significant differences were found while comparing SPARO test and SUPSO test results of freestyle cyclists and the reference group. Some of the differences were related to components, that smartly expresses specificity of freestyle cyclists´ mentality. Elite freestyle riders´ general and pre-competition mentality is specific, which is caused by specificity of this extreme cycling discipline. There are numerous factors that impact these athletes during the competition, more than in any other of cycling disciplines. Psychological preparation of freestyle cycling athletes would contribute to improve their performance.